Surface hydrophobicity of the rat colonic mucosa is a defensive barrier against macromolecules and toxins - Lugea, A (2000)
BACKGROUND—Mucosal surface hydrophobicity is a key factor of the gastric acid defence barrier. In the colon, surface hydrophobicity is high but its biological function remains unexplored. AIMS—To investigate the functional changes of the barrier due to removal of the surface active phospholipid layer by a detergent, or to reinforcement of the surface active phospholipid by local application of a suspension of lipids. METHODS—Surface hydrophobicity (contact angle measurement), colonic permeability (lumen to blood clearance of mannitol and dextran), and mucosal resistance against luminal aggression (distal colitis induced by dextran sodium sulphate, DSS) were investigated in three study groups: (a) rats pretreated with a detergent (Brij 35) known to remove surfactant lipids; (b) rats pretreated with a suspension of surface active lipids (tripalmitin and dipalmitoyl-phosphatidylcholine); and (c) control rats pretreated with the corresponding vehicles. RESULTS—In controls, surface hydrophobicity was low on the caecal mucosa and high in colon and rectum. Detergent treatment reduced surface hydrophobicity, and increased colonic permeability to mannitol and dextran. Conversely, treatment with lipids increased surface hydrophobicity, and reduced colonic permeability. Administration of DSS induced a progressive loss of colonic surface hydrophobicity, and an increase in permeability to mannitol and dextran. Detergent treatment increased susceptibility to epithelial damage and mucosal inflammation by DSS. Treatment with lipids reduced susceptibility to DSS colitis. CONCLUSION—Colonic surface hydrophobicity modulates permeability to hydrophilic molecules and protects against toxins.   Keywords: mucosal surface hydrophobicity; mannitol; dextran